Peranan Guru Dalam Meningkatkan Nilai Karakter Disiplin Dan Kejujuran Siswa Di SD Unggul Lampeunerut - Putry Julia; Ati Ati (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
This research entitle the Role of Teachers in increasing the character value of discipline and honesty of students at SD Unggul Lampeunuerut on Desember, 27-29, 2017. The purpose of this study is to know the role of the teachers in improving the character value of discipline and honesty of students at SD Unggul Lampeunerut. The research method used is a qualitative approach with descriptive quantitative. The results of the study showed that 83% of the teachers did not agree and had an effort to improve the character value of discipline and honesty of the students while only 17% agreed to do so. In conclusion, the teachers have a very large role in the role of teachers in improving the character value of discipline and honesty of students at SD Unggul Lampeunerut